ความต้านการแตกในฟันที่ได้รับการรักษาคลองรากฟันที่มีปริมาณเนื้อฟันที่เหลืออยู่ แตกต่างกันหลังจากเสริมผนังคลองรากฟันด้วยเรซินคอมโพสิตร่วมกับการบูรณะด้วยเดือยสำเร็จรูปและชนิดของเรซินคอมโพสิตที่แตกต่างกัน - สิริลักษณ์ เจริญวิริยะกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
This objective of this study was to compare the fracture resistance of endodontically treated teeth which had various dentinal wall thickness restored with fiber reinforced post and different resin composites and different resin cements. Endodontic preparation was performed on seventy mandibular second premolars. The tooth was decoronated and divided into 7 groups (n=10). Group 1 : dentinal wall was prepared correspond to D.T.Light post No.1. Group2, 3, and 4 had remaining dentinal wall thickness about 2 mm, 1.5mm and 1mm, respectively. All of the groups were restored with No.1, D.T.Light post and Multicore flow resin composite and Super-Bond C&B resin cement as luting agent. Group 5: remaining dentinal wall was about 1 mm and restored as group 1-4, except resin composite foundation used was experimental composite. Group 6 and 7: remaining dentinal wall was about 1 mm and restored as group 1-4 except Panavia F2 and no resin cement were used, respectively. Specimens were mounted in acrylic blocks with a 0.2 mm layer of silicone sealant covering the root. The vertical load was applied on the top of the specimen with cross head speed of 2 mm/min. Fracture resistance was measured on a universal testing machine. The fracture load in N of all groups were analyzed using ANOVA at p<0.05 to compare group 1-4 and Independent samples test was used to compare between group 4 and 5. Robust test of quality of mean (Welch) at p<0.05 was used to compare group 4, 6, 7. Various dentinal wall thickness, different resin composites and resin cement did not affect fracture resistance. Group 7 was statistically significant lower than group 4 (p<0.05). Fracture mode were similar among groups 1 to 4 and 6. Fracture mode was commonly found within core and between resin composite and dentin about 50-80%. In group 7 fracture mode was found only within core. The present study concluded that fracture resistance of endodontically treated teeth with various thickness of dentinal wall restored with different resin composites were not statistically significant difference.